Improving Students’ self-directed learning through visual novel games: its effectiveness and potential - Prayogi, Mochamad Danuadjie; Prihatin, Titi (Indonesian Journal of Curriculum and Educational Technology Studies, 2024)
The Merdeka Curriculum introduces Natural and Social Science (NSP)/Ilmu Pengetahuan Alam dan Sosial (IPAS) subjects to improve science literacy among primary school students. However, in one of the public elementary schools in Semarang, teachers still dominantly use the lecture method and textbooks, causing the science understanding of class 5A students in the 2023/2024 school year to remain low, as seen from the unsatisfactory results of daily tests and STS. This study aims to develop learning media through IPAS-based visual novel educational games with a Development Research approach using the ADDIE method and a one-group pretest-posttest research design. The sample consisted of 30 students from class 5A who were selected by purposive sampling. The game media was developed using the Ren'Py application and validated by media and material experts. The validation results showed the game had a very high level of validity. The effectiveness test showed increased self-directed learning with an N-Gain value of 0.73, indicating that the game is quite effective. The visual novel game ‘Earth and Environment’ is expected to help teachers overcome the limitations of digital media in IPAS learning and improve students' self-directed learning ability.